2024
DOI: 10.17398/2952-2218.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects on strength, jumping, reaction time and perception of effort and stress in men´ s top-20 World Padel Competitions

Álvaro Bustamante-Sánchez,
Ana Ramírez-Adrados,
Tamara Iturriaga
et al.

Abstract: Paddle tenis has experienced significant growth in recent years, becoming one of the most popular and globally expanding sports. This study aims to examine the physiological performance and subjective perception of stress and fatigue in top-20 padel players during matches. Seven elite players participated in the study. Various variables were evaluated, such as subjective perception of effort and stress, isometric grip strength, reaction time, and jump performance, both before and after the matches. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… Souza et al (2019) observed elevated somatic anxiety, LH/HF ratio, and cortisol levels preceding competitions in contrast to training, what suggest an excitement of the autonomous nervous system on its sympathetic division. As relevant competitions approach, as exemplified in our study with training occurring 2 weeks prior to a key event, research suggests an increase in stress and anxiety levels among athletes ( Loupos et al, 2008 ; Morales et al, 2014 ; Bustamante-Sánchez et al, 2024 ). In racket sports, contemporary methodologies advocate for competitive training scenarios mirroring match-play conditions to enhance decision-making proficiency in authentic settings ( Mecheri et al, 2019 ; Navia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“… Souza et al (2019) observed elevated somatic anxiety, LH/HF ratio, and cortisol levels preceding competitions in contrast to training, what suggest an excitement of the autonomous nervous system on its sympathetic division. As relevant competitions approach, as exemplified in our study with training occurring 2 weeks prior to a key event, research suggests an increase in stress and anxiety levels among athletes ( Loupos et al, 2008 ; Morales et al, 2014 ; Bustamante-Sánchez et al, 2024 ). In racket sports, contemporary methodologies advocate for competitive training scenarios mirroring match-play conditions to enhance decision-making proficiency in authentic settings ( Mecheri et al, 2019 ; Navia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 94%
“…The global surge of padel, a doubles racket sport, has attracted participants from over 60 nations affiliated with the International Padel Federation (2024) . This growth has triggered a notable rise in scholarly research focused on psychophysiology ( Conde-Ripoll et al, 2023 ; Díaz-García et al, 2023a ; Bustamante-Sánchez et al, 2024 ), although technical-tactical performance remains a dominant area of study ( Lupo et al, 2018 ; Escudero-Tena et al, 2021 ; Martín-Miguel et al, 2023 ; Conde-Ripoll et al, 2024 ; Ungureanu et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, competitive anxiety and self-confidence, specially prior to competition, has been extensively studied in recent decades ( 15 17 ). Research has shown that athletes with elevated anxiety levels often demonstrate poorer performance in competitions in comparison to those with lower anxiety levels ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%